The Agricultural cooperatives in the Albanian economy 1945-1985 (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2026)
The article aims to understand the management and operation of agrarian cooperativism in Albania under the administration of the Labor Party. Under the parameters of historical research in documentary mode and with the historical-logical method supported by chronological and geographical sub-methods, the development of these associations has been verified considering the seven Five-Year Plans and the influence that allied powers maintained in part of this stage, as well as the international isolation that affected the machinery technology necessary to develop the field. Other problems detected were the settlement of private plots of cooperative members and the stagnation in the reduction of the gaps between the rural environment and the urban environment. It is concluded that, despite these limitations, there was an increase in production through cooperativism, considering the previous backwardness of a feudal state and the national destruction caused by the Second World War.
Keywords: agrarian cooperatives; cooperatives; management